W-Band Near-Field Microscope - Guangbin Dai; Guoshuai Geng; Xiaoxuan Zhang; Jie Wang; Tianying Chang; Hong-Liang Cui (IEEE Access, 2019)
A home-built scattering-type scanning near-field millimeter-wave microscope based on a 110-GHz continuous-wave solid-state source is demonstrated with a spatial resolution of 1 μm, approximately 1/3000 of the incident wavelength, and a signal-to-noise ratio of 23.8 dB. The relationship between the length of the tip (antenna) and the wavelength for resonant enhancement, and the near-field distribution around the tip apex at different tip-sample separations were explored using finite-difference time-domain electromagnetic simulations to facilitate the design of the microscope. The dependence of the spatial resolution on the tip-sample separation and the harmonic order of the modulation frequency at which the near-field signal was extracted has been investigated experimentally and discussed in terms of the signal-to-noise ratio and the standard deviation of the demodulated signal.